The effect of augmented reality-assisted discovery learning model on digital literacy and cognitive knowledge about fungi - Putri Amanda Revalestina; Hadi Suwono (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The 21st century represents a time of worldwide interconnectedness that demands every individual to have digital knowledge and literacy. Science learning activities are important to help students learn and understand science and students' digital literacy. Learning that actively involves students will encourage students to find ideas. This study aims to investigate how the implementation of the discovery learning model, supported by digital tools, influences digital literacy and understanding of fungi content. The participants involved in this research consisted of two sets of 10th-grade students from SMAN 1 Kepanjen in Malang regency, East Java, which included a control group (X 8) and an experimental group (X 3). The approach for gathering data employed a pretest-posttest design for non-equivalent control groups. questionnaires, and learning reflection essays. Data analysis research used SPSS.25 assistance, including validity tests, reliability tests, prerequisite tests (Shapiro-Wilk normality and homogeneity), and hypothesis tests. According to the outcomes from data evaluation conducted through ANCOVA shows a sig level of <p = 0.005, this indicates that the null hypothesis H0 is dismissed while the alternative hypothesis H1 is accepted, suggesting that the Augmented Reality-assisted discovery learning model has an effect in fungi material on digital literacy and cognitive knowledge. The outcomes of the reflection essay by students show that learning can add new knowledge, improve understanding, motivate students, and actively seek new information in learning.